May of 68 or the prophecy of the end of Education - Villa, Fernando Gil (Revista Hipótese, 2016)
This papers aims to understand what is involved around one of the most interesting enigmas of our time: Why today is not given another May of 68 since there are the same reasons but stronger, outrageously stronger?.
Keywords: Freedom; University; Inequality; Democracy